Life of Moscheles, Volume 2 with selections from his diaries and correspondence - Moscheles, Charlotte 1805-1889 (Cambridge library collection. Music, 2014)
Born in Prague, pianist and composer Ignaz Moscheles (1794–1870) studied in Vienna and rapidly became a central figure in European musical life. He lived and worked in London for twenty-five years, leaving in 1846 to become principal professor of piano at the Leipzig Conservatoire at the invitation of his great friend Mendelssohn. As a pianist, he was renowned for his incisive technique rooted in the tradition of Clementi, and also much admired for his extempore performances. As a composer his output was mainly for the piano, and his studies are still in use today. First published in 1872–3, this lively biography, compiled from his diaries and letters by his wife Charlotte, records his dealings with and feelings about many great musicians of the nineteenth century. Reissued here is the 1873 English translation by Arthur Duke Coleridge, founder of the Bach Choir. Volume 2 covers 1836 to 1870, and includes a list of works